The association of dietary inflammatory index with sleep outcomes: A systematic review - Mona Golmohammadi; Mehnoosh Samadi; Yahya Salimi; Seyed Mostafa Nachvak; Vahideh Ebrahimzadeh Attari (Tabriz University of Medical Sciences, 2024)
Background: Sleep is a vital physiological process that plays a crucial role in various aspects of human health and well-being. Regarding the important role of diet on the sleep quality, the present study aimed to assess the association of dietary inflammatory index (DII) with the sleep outcomes and also to provide the potential mechanisms of action. Methods: PubMed, Web of Science and Scopus databases and Google Scholar search engine were systematically searched for relevant studies related to DII and sleep outcomes using appropriate search terms until February 2024. Results: From the initial systematic search of databases, 197 studies were retrieved. However, only 14 of them met the criteria for evaluation. Out of these, eleven studies indicated a significant correlation between higher DII scores and poor overall sleep quality and/or short/long sleep duration or its subscales. On the contrary, four studies did not find any proof of this association. Conclusion: This systematic review indicated that following an anti-inflammatory diet could potentially lead to an improvement in the sleep outcomes. Well-designed clinical trials in the future will be necessary to provide a better understanding and quantification of this association.